Internal and external load of youth soccer players during small-sided games - Dimitriadis, Y.; Michailidis, Y.; Mandroukas, A.; Gissis, I.; Mavrommatis, G.; Metaxas, T. (Trends in Sport Sciences, 2022)
Introduction. A majority of soccer players are engaged in recreational sport and particularly in developmental soccer: it seems necessary to assess the internal and external load of small- -sided games (SSGs) of this specific group in view of the scarce scientific data on the subject. Aim of Study. The aim of the study was to investigate the internal and external load of youth soccer players during SSGs with different numbers of players and field dimensions. Material and Methods. The total sample consisted of 16 youth recreational under-15 soccer players. The participants performed SSGs (1v1, 2v2, 3v3, 4v4 with goalkeepers) at an individual playing area of 1:150 m², 1:100 m², and 1:75 m² in random order. They wore portable GPS (Polar Team Pro) tracking sensors in order to record internal and external loads during the whole training session. All participants were asked to rate the RPE at the end of SSGs. The significance level was set at p < 0.05. Results. The results showed that SSGs with a smaller number of players and a larger individual playing area led to an increasing internal load. The external load analysis in the present study showed that SSGs with a higher number of players and a larger individual playing area had a more significant impact on the external load. Conclusions. In conclusion, the number of players and field dimensions should be taken into account by coaches during SSGs so as to achieve the ideal training organization and as an implementation of the training sessions, competitive microcycle, and yearly planning.